2014
DOI: 10.1128/genomea.00091-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Vibrio anguillarum Phage CHOED Successfully Used for Phage Therapy in Aquaculture

Abstract: Vibrio anguillarum phage CHOED was isolated from Chilean mussels. It is a virulent phage showing effective inhibition of V. anguillarum. CHOED has potential in phage therapy, because it can protect fish from vibriosis in fish farms. Here, we announce the completely sequenced genome of V. anguillarum phage CHOED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The CHOED bacteriophage that naturally infects the V. anguillarum PF4 strain is a lytic phage belonging to the Podoviridae family and was isolated from molluscs in southern Chile (Higuera et al, 2013). Its genome has been sequenced previously (Romero et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The CHOED bacteriophage that naturally infects the V. anguillarum PF4 strain is a lytic phage belonging to the Podoviridae family and was isolated from molluscs in southern Chile (Higuera et al, 2013). Its genome has been sequenced previously (Romero et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Romero et al . () demonstrated that Chilean mussels naturally produced V. anguillarum ‐specific Podoviridae ‐phage CHOED in situ and in vitro (Higuera et al . ).…”
Section: Closing Remarksmentioning
confidence: 97%
“…Ultimately with time, aquaculture will stray from its present practices and evolve to more resemble natural, functional marine habitats. Romero et al (2014) demonstrated that Chilean mussels naturally produced V. anguillarum-specific Podoviridae-phage CHOED in situ and in vitro (Higuera et al 2013). If facilities cultured such submerged organisms as Chilean mussels in the bottom of each aquaculture tank, healthy fish masses could be produced naturally without the need for commercialized chemicals.…”
Section: Future Researchmentioning
confidence: 99%
“…Studies on V. anguillarum -specific bacteriophages have so far mainly focused on lytic phages and their potential use in phage therapy application [ 30 , 31 , 32 ] while very little is known about the role of temperate phage-encoded virulence and other fitness factors as drivers of functional dynamics in V. anguillarum . Improving our understanding of how phages may influence the genomic and phenotypic characteristics of V. anguillarum thus requires more detailed knowledge of the genetic properties and dispersal of temperate phages infecting this pathogen as well as their distribution as prophages in the host community.…”
Section: Introductionmentioning
confidence: 99%